Self-isolation at the dacha: Can’t? Can? Have to? - Uliana G. Nikolaeva; Alexander V. Rusanov (Население и экономика, 2020)
Measures taken by most countries to limit the coronavirus infection spread include self-isolation. An option of voluntary restriction of personal contacts for citizens is to move to the country (second or third) houses, which have a particular name in Russia – “dacha”. The demand for country estates as places of self-isolation can be assessed as the emergence of a new sanitary-epidemic function in second homes. Institutional management of such movements in connection with the coronavirus pandemic varies by country, ranging from prohibition (Norway) to encouragement (Belarus), and quantitative indicators (mass character or singleness) fluctuate according to lifestyle, national traditions, characteristics of settlement, urban housing policy, public health opportunities and many other factors. For Russians, the migration of residents of megalopolises from the city to country houses was a reaction to the pandemic, a characteristic social-group strategy of health-preserving behaviour. Several million Muscovites, Petersburgers, as well as residents of other megacities of Russia moved outside the cities immediately after the outbreak of the pandemic. “Half-townspeople” – internal migrant workers and “seasonal workers” (workers living in villages or small towns but working in metropolises in watch mode) also moved to rural areas. The mass nature of centrifugal spatial-migratory deurbanization model of behaviour of Russians during the pandemic is determined by the specifics of the spatial distribution of the population in Russia, historical features of urbanization and deurbanization processes, in particular, the widespread distribution of second (and third) country houses (dachas) among the citizens. Russia leads both in relative and absolute number of dacha dwellers among the European countries. The number of country houses in Russia is estimated by specialists at 17–20 million, and the number of dacha dwellers at 50–60 million; at least half of the citizens have second (and often third) country houses. Massive movements of citizens into out-of-town spaces had both positive and negative consequences. A significant share of citizens reduced risks of infection and were able to avoid “imprisonment” within the apartment with accompanying socio-psychological overload and physical inactivity. However, mass movements also contributed to the rapid spread of coronavirus beyond the original foci. The article considers the approaches of European countries to countryside self-isolation, describes chronicles of restriction on movement of citizens in Russian regions and waves of summer migration during the pandemic, suggests an assessment of dacha migration from the capital, and discusses its short-term socio-economic consequences.